Estudo da densidade de corrente crítica para reversão da magnetização de nanoelementos ferromagnéticos - Souza, Rafaela Medeiros de (2015)
The discovery that a spin-polarized current is capable of exerting a torque in a ferromagnetic material, through spin transfer, might provide the development of new technological devices that store information via the direction of magnetization. The reduction of current density to revert the magnetization is a primary issue to potential applications on non volatile random access memories (MRAM). We report a theorical study of the dipolar and shape effects on the critical current density for reversal of magnetization, via spin transfer torque (STT), on ferromagnetic nanoelements. The nanostructured system consists on a reference layer, in which the current will be spin-polarized, and a free layer of magnetization reversal. We observed considerable changes on the critical current density as a function of the element’s reversion layer thickness (t = 1.0 nm, 1.5 nm, 2.0 nm e 2.5 nm) and geometry (circular and elliptical), the material kind of the system free layer (Iron and Permalloy) and according to the orientation of the magnetization and the spin polarization with the major axis. We show that the critical current density may be reduced about 50% by reducing the Fe free layer thickness and around 75% when we change the saturation magnetization of circular nanoelements with 2.5 nm of thickness. We still observed a reduction as much as 90% on the current density of reversion for thin nanoelements magnetized along the minor axis direction, using in-plane spin polarization parallel to the magnetization.